Study of Milton Glaser's Creative Process In Creating Design - Setiawan, Hendra (Universitas Ciputra, 2018)
Those in the art and design field, such as graphic designers, should be creative and inspired, and they usually have their own ways to be creative. Yet, some designers are considered to be so outstanding that they receive such recognition in their creative process. One of them is Milton Glaser. He has been considered one of the first rank designers for decades. Therefore, it is really appropriate and wise for young designers to recognize Glaser’s creative process in order that they could learn and be inspired by his experience. This study focuses in the examination of Milton Glaser’s creative process gained from interviews conducted by the media. The short-term goal of this study is to learn the creative process of a design expert, which hopefully would inspire and open the mind of young designers in their work. After gaining inspiration from this creative process, hopefully the young designers would be much more creative and easily inspired in developing their idea, which is the long-term goal of this study.